CERCUL HERMENEUTIC: PREMISE METODOLOGICE - Ursu, Cristina (CEP USM, 2021)
The process of reading and re-reading is sequential, temporal. We first understand the constituent parts whose context is mediated by expectations, designs, conjunctures that can be unconscious associations. In this article we wonder if before reading the whole text itself, students can exchange their own derrived texts in order to see the multitude and diversity of the whole starting from a single part/ sequence of the text. Could our own whole, consisting of a sequence of text, “absorb” our prejudices and open us to the thing itself, the text itself?
THE HERMENEUTIC CIRCLE: METHODOLOGICAL PREMISES
Keywords: hermeneutic circle; conjunctures; close reading